2023
DOI: 10.1111/pirs.12731
|View full text |Cite
|
Sign up to set email alerts
|

Cultural heritage sites, tourism and regional economic resilience

Abstract: The paper explores the role of tourism demand and cultural World Heritage Sites on the regional economic resilience among European Union countries. The results pinpoint to the importance of cultural World Heritage Sites in keeping the regional economic resilience. The results on tourism demand are not unambiguous—domestic tourist arrivals play a significantly positive role while inbound tourist arrivals negatively affect regional economic resilience. Cultural tourism, defined as the joint effect of tourism and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Based on a review of the related literature, international scholars have studied ICH through theoretical constructs and discussions [3]. They explored concepts and protection mechanisms [4,5], as well as shared practical experience in the management and development of ICH [6,7]. Presently, Chinese scholars have mainly studied the concept [8,9], classification [10], and utilization, as well as protection, of ICH [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Based on a review of the related literature, international scholars have studied ICH through theoretical constructs and discussions [3]. They explored concepts and protection mechanisms [4,5], as well as shared practical experience in the management and development of ICH [6,7]. Presently, Chinese scholars have mainly studied the concept [8,9], classification [10], and utilization, as well as protection, of ICH [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…As per the discoveries presented by Figueroa et al (2018), the attraction of international tourists hinges on optimizing tourist influxes, encompassing cultural richness, activities, and natural assets. Studies have indicated that visitors are more inclined towards renowned locations with elevated historical, cultural, creative, food tourism, and aesthetic worth (Li & Kovacs, 2023;Muštra et al, 2023;Seongseop et al, 2021).…”
Section: Introductionmentioning
confidence: 99%